Metamorphoses of Lyme disease spirochetes: phenomenon of Borrelia persisters - Rudenko, Natalie; Golovchenko, Maryna; Kybicova, Katerina; Vancova, Marie (Parasites & vectors, 2019)
The survival of spirochetes from the Borrelia burgdorferi (sensu lato) complex in a hostile environment is achieved by the regulation of differential gene expression in response to changes in temperature, salts, nutrient content, acidity fluctuation, multiple host or vector dependent factors, and leads to the formation of dormant subpopulations of cells. From the other side, alterations in the level of gene expression in response to antibiotic pressure leads to the establishment of a persisters subpopulation. Both subpopulations represent the cells in different physiological states. "Dormancy" and "persistence" do share some similarities, e.g. both represent cells with low metabolic activity that can exist for extended periods without replication, both constitute populations with different gene expression profiles and both differ significantly from replicating forms of spirochetes. Persisters are elusive, present in low numbers, morphologically heterogeneous, multi-drug-tolerant cells that can change with the environment. The definition of "persisters" substituted the originally-used term "survivors", referring to the small bacterial population of Staphylococcus that survived killing by penicillin. The phenomenon of persisters is present in almost all bacterial species; however, the reasons why Borrelia persisters form are poorly understood. Persisters can adopt varying sizes and shapes, changing from well-known forms to altered morphologies. They are capable of forming round bodies, L-form bacteria, microcolonies or biofilms-like aggregates, which remarkably change the response of Borrelia to hostile environments. Persisters remain viable despite aggressive antibiotic challenge and are able to reversibly convert into motile forms in a favorable growth environment. Persisters are present in significant numbers in biofilms, which has led to the explanation of biofilm tolerance to antibiotics. Considering that biofilms are associated with numerous chronic diseases through their resilient presence in the human body, it is not surprising that interest in persisting cells has consequently accelerated. Certain diseases caused by pathogenic bacteria (e.g. tuberculosis, syphilis or leprosy) are commonly chronic in nature and often recur despite antibiotic treatment. Three decades of basic and clinical research have not yet provided a definite answer to the question: is there a connection between persisting spirochetes and recurrence of Lyme disease in patients?
Keywords: recidiva; Borrelia burgdorferi; Antibiotic treatment; Humans; Lyme disease; Round bodies; Dormant forms; mikrobiální viabilita; Borrelia burgdorferi Group; Lyme Disease; lymeská nemoc; lidé; antibakteriální látky; Microbial Viability; Anti-Bacterial Agents; Borrelia burgdorferi komplex; biofilmy; Biofilm; Persisters; Persistent infection; Recurrence; Biofilms